The differences in transmission properties of two bird calls show relation to their specific functions - Piza Duarte, Paola (2016)
When vocalizations transmit throughout the environment, attenuation and degradation may change the information of the signal; the loss of information is related to changes in both frequency and duration of vocalizations. The variation in frequency and duration of bird calls is related to the functions of each call type. Using a sound transmission experiment, the authors tested the transmission properties of two call types both produced by white-eared ground-sparrows Melozone leucotis; these calls vary in frequency and duration, suggesting that they may transmit at different distances. The authors broadcasted and re-recorded each call type at four different distances (4, 8, 16, and 32 m) inside ground-sparrow territories. The authors found that calls with a narrow bandwidth and longer duration transmitted at longer distances, and showed a lower attenuation and degradation than the calls with a broad bandwidth and shorter duration. These results support the relationship between the transmission properties of a call and the different functions (short and long distance communication) also evidence how the selection of these calls facilitates the communication over different distances.